Comparative effectiveness of umeclidinium/vilanterol versus indacaterol/glycopyrronium on Moderate-to-severe exacerbations in patients with chronic obstructive pulmonary disease in clinical practice in England - Requena, Gema; Czira, Alexandrosz; Banks, Victoria; Wood, Robert; Tritton, Theo; Castillo, Catherine; Yeap, Jie; Wild, Rosie; Compton, Chris; Rothnie, Kieran J.; Herth, Felix; Quint, Jennifer; et al. (The International journal of chronic obstructive pulmonary disease, 2023)
Purpose: Chronic obstructive pulmonary disease (COPD) exacerbations are associated with significant morbidity and mortality and increased economic healthcare burden for patients with COPD. Long-acting muscarinic antagonist (LAMA)/long-acting β2-agonist (LABA) dual therapy is recommended for patients receiving mono-bronchodilator therapy who experience exacerbations or ongoing breathlessness. This study compared two single-inhaler LAMA/LABA dual therapies, umeclidinium/vilanterol (UMEC/VI) and indacaterol/glycopyrronium (IND/GLY), on moderate-to-severe exacerbation rates in patients with COPD in England. Patients and Methods: This retrospective cohort study used linked primary care electronic health record data (Clinical Practice Research Datalink-Aurum) and secondary care data (Hospital Episode Statistics) to assess outcomes for patients with COPD who had a first prescription for single-inhaler UMEC/VI or IND/GLY (index date) between 1 January 2015 and 30 September 2019 (indexing period). Analyses compared UMEC/VI and IND/GLY on moderate-to-severe, moderate, and severe exacerbations, healthcare resource utilization (HCRU), and direct costs at 6, 12, 18, and 24 months, and time-to-first on-treatment exacerbation up to 24 months postindex date. Following inverse probability of treatment weighting (IPTW), non-inferiority and superiority of UMEC/VI versus IND/GLY were assessed. - Results: In total, 12,031 patients were included, of whom 8753 (72.8%) were prescribed UMEC/VI and 3278 (27.2%) IND/GLY. After IPTW, for moderate-to-severe exacerbations, weighted rate ratios were <1 at 6, 12, and 18 months and equal to 1 at 24 months for UMEC/VI; around the null value for moderate exacerbations and <1 at all timepoints for severe exacerbations. UMEC/VI showed lower HCRU incidence rates than IND/GLY for all-cause Accident and Emergency visits and COPD-related inpatient stays and associated all-cause costs at 6 months post-indexing. Time-to-triple therapy was similar for both treatments. - Conclusion: UMEC/VI demonstrated non-inferiority to IND/GLY in moderate-to-severe exacerbation reduction at 6, 12 and 18 months. These results support previous findings demonstrating similarity between UMEC/VI and IND/GLY on reduction of moderateto-severe exacerbations.